A Gamification–Motivation Design Framework for Educational Software Developers. (September 2018) - Buckley, Jim; DeWille, Tabea; Exton, Chris; Exton, Geraldine; Murray, Liam
Gamification is the use of game design elements in nongame contexts and has been shown to be effective in motivating behavior change. By seeing game elements as "motivational affordances, " and formalizing the relationship between these elements and motivational affordances, it is the position of this article that gamification can be effectively applied to improve software systems across many different application domains. The research reported here aims to formalize the relationship between game elements and motivation, toward making gamification's use more systematic. The focus is on the development of a framework linking commonly occurring game elements with the components of a psychological motivational model known as the self-determination theory, coupled with a proposed framework of commonly occurring game elements. The goal is to inform system designers who would like to leverage gamification of the game elements they would need to employ as motivational affordances.